2010
DOI: 10.4141/cjps09077
|View full text |Cite
|
Sign up to set email alerts
|

Grafting as a tool in common bean breeding

Abstract: . 2010. Grafting as a tool in common bean breeding. Can. J. Plant Sci. 90: 299Á 304. Compatibility of rootstock for grafting was investigated in four species of Phaseolus to study the use of grafting as a tool in bean breeding programs. Four genotypes of Phaseolus vulgaris and one genotype of P. coccineus were used as rootstocks. Two genotypes of P. vulgaris, and one each of P. acutifolius and P. angustissimus, and an interspecific hybrid of P. acutifolius )P. angustissiumus were used as scions. The common bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In legumes, grafting has been used extensively to study the effects of shoots and roots on nodulation control and plant growth within species such as soybean ( Glycine max) (Sheng and Harper, 1997), Lotus japonicus (Nishimura et al , 2002) and Medicago truncatula (Penmetsa et al , 2003). Gurusamy et al (2010) reported that grafting intra- and inter-specific scions onto compatible Phaseolus vulgaris rootstock had the potential to improve early generation seed increase ratio, multiplication of clones for screening and perpetuation of sterile or recalcitrant inter-specific hybrids for various common bean breeding strategies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In legumes, grafting has been used extensively to study the effects of shoots and roots on nodulation control and plant growth within species such as soybean ( Glycine max) (Sheng and Harper, 1997), Lotus japonicus (Nishimura et al , 2002) and Medicago truncatula (Penmetsa et al , 2003). Gurusamy et al (2010) reported that grafting intra- and inter-specific scions onto compatible Phaseolus vulgaris rootstock had the potential to improve early generation seed increase ratio, multiplication of clones for screening and perpetuation of sterile or recalcitrant inter-specific hybrids for various common bean breeding strategies.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo grafting was shown to be an efficient technique in the production of inter-specific hybrids in common bean (Gurusamy et al, 2010). Subsequently, Gurusamy et al (2011) showed that it was possible to successfully produce inter-generic in vivo grafts of scions of L. culinaris onto faba bean (Vicia faba L.) rootstocks.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Ten grafts and 10 rooted cuttings were made for each replication. The grafting and rooting procedures were the same as those reported by Gurusamy et al (2010) for common bean. For the lentil-faba bean experiment, rootstock preparation was the same as for other experiments.…”
Section: Grafting Proceduresmentioning
confidence: 95%
“…This is especially critical in cases where hybrids are difficult to produce, for example, in cases where barriers to pollination limit crossing success. Gurusamy et al (2010) showed that for common bean (Phaseolus vulgaris L.) grafted scions produced significantly more seed in comparison to ungrafted controls and rooted cuttings. From the perspective of a plant breeding program, this provides a tool to increase the number of F 1 meristems and the size of F 2 populations for rare or difficult crosses.…”
mentioning
confidence: 98%